The United States SPS and TBT Measures on Catfish: Arguments on the side of Vietnam - Phu, Tran Vang (The journal of contemporary issues in business and government, 2021)
The “catfish conflict” between Vietnam and the US was a crucial case for unbalanced relations between developing and developed countries. The conflict comprised two principal parts: (i) safety and phytosanitary (environmental and sanitary) measures; and (ii) technological trade barriers (catfish labelling regulations). This paper deals with and discusses the above two parts. The statements in this paper are based on WTO regulations, empirical evidence and personal data collected from 25 people in the Thot Not District of Can Tho City, Vietnam (i.e. fish farmers, producers and local authorities). The main purpose of this survey is to collect accurate information from relevant people on the side of Vietnam and verify data from other scientists on feed, fingerlings, methods for farming, catfish processing and so By evaluating the facts and arguments on the two sides, the paper will strive for two purposes: (i) deciding whether or not the U.S rules are consistent with World Trade Organization law; and ii) investigating whether Vietnam can carry the issue into the WTO dispute settlement mechanism and benefit.